Seroprevalencia de marcadores de infecciones transmisibles por vía transfusional en banco de sangre de Colombia (2012)
To determine the seroprevalence of markers of transfusion transmissible infections in donors of a blood bank in Medellin, Colombia, beteween 2007 and 2010